335 Low Frequency Oscillations in the Ventral Nucleus Accumbens Region Guides Brain Responsive Neurostimulation for Loss of Control Eating: An Initial Review of the BITES Trial. (1st March 2022) - Shivacharan, Rajat; Rolle, Cammie; Buch, Vivek; Barbosa, Daniel; Cunningham, Tricia; Safer, Debra; Bohon, Cara; Azagury, Dan; Dunn, Laura; Yutsis, Maya; Tass, Peter A.; Williams, Nolan R.; et al.
Abstract : INTRODUCTION: Loss of control (LOC) eating is pervasive in eating disorders and obesity. The presence of this phenotype appears to predict treatment-resistance, including gastric bypass surgery. Brain-responsive neurostimulation guided by low frequency changes in the nucleus accumbens (NAc-RNS) was previously found to block LOC eating behavior in mice. Following this novel preclinical work, the U.S. Food and Drug Administration approved an Investigational Device Exemption for a first-in-human study. METHODS: Two participants (female, 45 and 55 years old) with binge-eating disorder and morbid obesity (body mass index, 45 and 50 kg/m 2 ) refractory to gastric bypass were surgically implanted with a brain-responsive neurostimulator (RNS System; NeuroPace, Inc.) connected to bilateral NAc depth leads. NAc field potentials were recorded postoperatively in the clinic while the participants completed eating tasks. Outside of the clinic, participants maintained a diary describing their LOC episodes, specifically describing craving and satiety severity (Likert scale), and triggered the neurostimulator to record timestamped NAc field potentials. NAc field potentials and bilateral NAc connectivity were analyzed for the development and implementation of a novel NAc-RNS paradigm. RESULTS: In the clinic, the left ventral NAc region activity showed increased delta (2-4 Hz)- and theta (4-8 Hz)-band power during anticipatory bites of highly caloric, palatable food when compared to standard meal bites. In the ambulatory setting, we observed increased bilateral ventral NAc delta band activity and connectivity that appeared selective for states of food craving. Therefore, the RNS System was programmed to detect brief bursts of low-frequency activity in the bilateral ventral NAc, and delivered bilateral, bipolar stimulation (∼1 μC/cm 2 charge density per 10s stimulation bout). This paradigm resulted in decreased LOC episodes (∼25% in both participants) and subjective improvement in decision-making surrounding food choices. CONCLUSION: We present early findings of an electrographic signal associated with LOC eating with promising preliminary evidence of restored control using a NAc-RNS paradigm. Future directions include refining control signals, adaptive parameters, and examining the long-term effects of restoring inhibitory control on obesity.